Rethinking Boundaries: The Ftx Fiasco and The Imperative of Regulating Cryptocurrency Exchanges - Gulyev, Ramil (Annals of Spiru Haret University. Economic Series, 2024)
A turning point in the sector was the bankruptcy of FTX, a well-known cryptocurrency exchange, in late 2022. Sam Bankman-Fried founded FTX, which at first prospered with its cutting-edge offers. However, because of financial mismanagement and regulatory issues, FTX experienced a liquidity problem and widespread withdrawals. The collapse revealed regulatory shortcomings and generated demands for improved supervision and investor protection on a global scale. It is essential to implement swift changes, such as harmonized laws and transparent auditing, in order to reduce risks and promote market integrity. Nonetheless, regulatory obstacles continue to exist, necessitating a careful balancing act between innovation and supervision. The failure highlights the necessity of educating stakeholders and helping them adjust to the changing cryptocurrency environment. Regulations guarantee stability, investor trust, and institutional involvement, even though they may also present challenges. In the end, the crash of FTX steered the sector toward responsible expansion and emphasized the significance of strong regulatory frameworks in determining the course of cryptocurrency markets.